The communication habit : strategies that set you apart and leave a lasting impression - Katen, Laura Joan (McGraw-Hill, 2020)
"From quick conversations to awkward interactions-learn the communication strategies you need to distinguish yourself in any situation and progress your success! First impressions are made in seven seconds or less-so it's imperative that you make every moment count-and The Communication Habit shows you how to do it. One of today's leading experts in business communication explains how to identify and break communication habits-even well-intentioned ones-that impede success, and replace them with time-tested communication techniques that have been utilized by some of the most successful executives and entrepreneurs in the world. It provides a practical roadmap for applying the right communication tools and strategies in the most common business settings and situations, and for rebuilding and recovering from mistakes, damaged relationships, or negative impressions. Specific topics include: Building and Communicating Confidence Having a Voice and Being Heard Undermining Key Words and Phrases to Avoid Establishing & Articulating Your Value Acknowledging vs. Apologizing Leading with Empathy Strategies for Recovering, Rebuilding, and Re-Establishing"--